Stability and immunogenicity of hypoallergenic peanut protein–polyphenol complexes during in vitro pepsin digestion. Issue 7 (8th July 2015) - Plundrich, Nathalie J.; White, Brittany L.; Dean, Lisa L.; Davis, Jack P.; Foegeding, E. Allen; Lila, Mary Ann
<x xml:space="preserve">Abstract</x> Allergenic peanut proteins are relatively resistant to digestion, and if digested, metabolized peptides tend to remain large and immunoreactive, triggering allergic reactions in sensitive individuals.